A study on the unphysical mass transfer of SCMP pseudopotential LBM - Gong, Wei; Yan, Yuying; Chen, Sheng (Elsevier, 2018)
In general, a multi-bubble/droplet configuration cannot sustain a steady state using single-component multiphase (SCMP) pseudopotential lattice Boltzmann method (LBM). Our study shows that the unachievable multibubble/droplet system is for an unphysical mass transfer, which we call ‘‘the big eat the small” – the smaller bubbles/droplets shrink, and eventually disappear while the bigger ones get bigger without a physical coalescence. In our present study, the unphysical mass transfer phenomenon is investigated, and the possible reason is explored. It is found that there is a spurious flow field formed between two bubbles or droplets with different shapes, and such flow field is exactly the transfer of high-density mass. In addition, it is found that the curvatures of the interfaces determine the direction of the spurious flow field, and for the definition of ‘‘the big eat the small”, ‘‘the big” refers to the interfaces that have larger radii of curvature while ‘‘the small” represents the interfaces with smaller radii of curvature. Multi-component multiphase (MCMP) LBM is also tested in this work and it is found to be free of the unphysical mass transfer. Moreover, all the cases show that the most likely reason for the unphysical mass transfer might be the essential attractive interaction forces of the pseudopotential LBM.